Clast morphology of the Siwalik conglomerates from the Dhan Khola Formation, Surai Khola area, Mid-Western Nepal (Journal of Nepal Geological Society, 2000)
Clast morphology of the Siwalik conglomerates from the Dhan Khola Formation was studied at 19 horizons. The clasts were measured to calculate morphological indices such as axial ratios, c/a and (a-b)/(a-c), maximum projection sphericity (ψp), coefficient of flatness (CF), and roundness (p) separately for quartzite clasts (with two size-grades) and other clasts. The shape indices were plotted in shape diagrams and statistical tests were used to compare the shape indices of the above clasts with the index limits proposed in earlier studies.Based on clast type, four units are proposed for the Dhan Khola Formation. The formation is sub-divided into the volcanic clast-dominated, dolomite clast-dominated, quartzite clast-dominated, and terrigenous clast-dominated units, respectively from bottom to top. The latter unit contains many clasts derived from the Siwaliks. The quartzite clasts are more compact than other ones with significant differences in their axial ratios. The quartzite clasts show textural abnormalities and their p values decrease in the upper part of the formation suggesting high rate of sediment supply and nearness of complex source. The quartzite clasts with smaller (>-4ϕ) size-grade are better sphered. They plot clearly in the fluvial field of the ψp versus CF diagram. In 60 % of the quartzite clasts, means of ψp and CF exceed significantly the lower index limits showing that they were shaped in fluvial environment. However, the samples giving insignificant results could have also formed under the same conditions but with ψp and CF values lower than index limits proposed earlier.